Differences on post-fire regeneration of the pioneer trees Cecropia glazioui and Trema micrantha in a lowland Brazilian Atlantic Forest - Silva Matos, Dalva M (Universidad de Costa Rica, 2005)
A study of natural post-fire succession was carried out in a disturbed vegetation around fragments of the Atlantic Rain Forest (National Biological Reserve of Poço das Antas (22°30’-22°33’S, 42°15’-42°19’W), Rio de Janeiro State). All the pre-fire individuals of Cecropia and Trema in the area were numbered with plastic labels. In order to check for the presence of new sprouts and mortality, two other censuses were carried out, at 3 and 12 months after the fire. The dominant species were: Pteridium aquilinum, Panicum maximum, Trema micrantha and Cecropia glazioui. Few days after the passage of fire, grasses and ferns spread their area, while the stands of Trema and Cecropia were completely burned. Most of individuals of Cecropia produced some sprouts while most of individuals of Trema died. However, a great number of seedlings of Trema were recruited while only one single seedling of Cecropia were observed during a period of one year. Most of these seedlings died through the year while the sprouts were already reproducing. The uses of Cecropia in places where fire is recurrent could be more appropriate because of its higher chance of survival and faster recovering ability after fire